Prarancangan Pabrik Asam Asetat Dengan Proses Monsanto Kapasitas 120.000 Ton Per Tahun - , Darmanto, Hamid Abdillah, S.T., M.T, Emi Erawati, S.T., M.Eng (2017)
Acetic acid in Indonesia needs unmet by local producers, so it must be imported from abroad. This is due to the small number of acetic acid plant in the country. With established acetic acid plant is expected to meet the needs of acetic acid in the country to spur the development of industries that use it as raw material. Acetic acid plant as methanol carbonylation process capacity of 120.000 tonnes by year of operation for 330 days by year. The process of manufacturing acetic acid using methanol and carbon monoxide such as raw material. This process takes place in a bubble reactor with water as a coolant. The reaction takes place in the liquid-gas phase. Which is exothermic, irreversible with non-adiabatic isothermal operating conditions at a temperature of 177 ° C and a pressure of 30 atm. Methanol requirement of 8.135,94 kg/hr and carbon monoxide by 7.229,39 kg/hr. Products such as acetic acid at 15.182,10 kg/h. Utilities that include the provision of water obtained from river that is 13.628,18 kg/h, the steam requirement is 5.272,68 kg/h with the fuel requirement is 4.615,78 L/day for electricity requirement is obtained from the PLN and generator sets for 250 kW as reserve . While for compressed air requirement of 50 m3/hour. The factory was established in the industrial area of East Kalimantan, with a land area of 25.000 m2 with number of employees 160 people. This plant requires fixed capital amount Rp. 785. 457. 962. 777 and working capital. Rp 455. 970. 978.794. From the economic analysis of this plant demonstrates a profit before tax of Rp. 403. 389. 987. 571 by year and profit after tax of 50% is Rp. 201. 694. 993. 785 by year. Percent of Return On Investment (ROI) before tax after tax is 51,35% and 25,67%. Pay Out Time (POT) before tax is 1,62 year and after tax is 2,80 year. Break Event Point (BEP) is 40,60%, Shut Down Point (SDP) is 27,94% and the Internal Rate of Return (IRR) is 34,93%.